Solar submillimeter and gamma-ray burst emission - Kaufmann, Pierre (2002)
Solar flare emission was measured at 212 GHz in the submillimeter range by the Submillimeter Solar Telescope in the 1.2-18 GHz microwave range by the Owens Valley Solar Array and in the gamma-ray energy range (continuum) by experiments on board the Yohkoh (>1.2 MeV) and Shenzhou 2 (>0.2 MeV) satellites. At the burst onset, the submillimeter and microwave time profiles were well correlated with gamma rays to the limit of the temporal resolution (≤10 s). At 212 GHz, fast pulses (<1 s), defined as time structures in excess of the bulk emission, were identified as the flux increased. Their spatial positions were scattered by tens of arcseconds with respect to the main burst emission position. Correlation of submillimeter emission with gamma-ray fast time structures shorter than 500 ms is suggested at the gamma-ray maximum. The time variation of the rate of occurrence of the submillimeter rapid pulses was remarkably well correlated with gamma-ray intensities in the energy range (>1.2 MeV), attaining nearly 50 pulses per minute at the maximum. These results suggest that gamma rays might be the response to multiple rapid pulses at 212 GHz and might be produced at different sites within the flaring region.